Future Control Room Improvements schemes : government update on fire and rescue authority schemes : Ex-Fire Regional Control Centres - marketing and disposal.: government update on fire and rescue authority schemes : Ex-Fire Regional Control Centres - marketing and disposal. (December 2015) - Great Britain., Department for Communities; Local Government,
No abstract available